Pertimbangan Pengambilan Pajak dari Pemilik Bitcoin di Indonesia - Sinta Anggraeni (Jurnal Hukum Ekonomi Syariah, 2022)
In this modern era, sellers will do their best to have people purchase their things. Globalisation era has a strong connection to advanced technologies. It is not only science that gets more advanced, almost every aspect in modern society will grow and develop better and better. Nowadays, peopla do not only use physical currency such as coins and money. People now are being exposed to Bitcoin. It is a new means of transaction that has been widely known for the last 4 years. Digital money such as bitcoin kind of has complicated calculation, thus its nominal gets bigger and bigger each year. This bitcoin phenomenon is not only popular in indonesia. Some other countries even try to ban it. However, there are more countries that make bitcoin legal. In indonesia, bitcoin users are not proected by any laws if some unexpected circumtances happen. The reason why cryptocurrency is not legal yet in Indonesia is because bitcoin cannot be easily taxed. It happens because bitcoin is used without any third party; only between bitcoin beholders. The country and its financial departments cannot intervene. Thus, they cannot tax bitcoin beholders, which commonly hold huge nominals that can reach million hundreds of rupiah.